The Utilitarian Stigma of Environmental Protection - Wawrzyniak, Jan R. (Conatus - Journal of Philosophy, 2019)
In this paper I want to point out the multifaceted impact of utilitarianism as well as pragmatism, applied as the unified philosophy of environmental protection. Special attention is paid to the utilitarian aspect of Marxism, and a continuous (1988-2018), comprehensive case study from Poland – in the context of European economic realities – serves as an example of social receptionof the utilitarian paradigm in contemporary environmental protection policy.